2019
DOI: 10.1007/s42452-019-1049-4
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of lipid nanosystems containing omega-3 fatty acids and resveratrol in textile substrates for wound healing and anti-inflammatory applications

Abstract: In the present work, lipid nanosystems containing omega-3 fatty acid (nanostructured lipid carriers, NLCs) or omega-3 fatty acid and resveratrol (liposomes) were developed to improve cotton textile substrates as dressings with anti-inflammatory properties for wound healing applications. Lipid nanosystems were incorporated into woven, non-woven and knitted cotton substrates by exhaustion and impregnation. Based on physical-chemical characterization of the textile substrates, the textile structure and type of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Additionally, another key point regarding the development of therapeutic textiles with antimicrobial activity to target skin dysbiosis is the composition of such products; unfortunately, most of them comprise synthetic or metallic antimicrobial agents, which, despite being very effective against a range of microorganisms and providing durable effects on textiles, are a concern due to health hazards, action on non‐target microorganisms and environmental pollution 37,41 . Consequently, the incorporation of natural bioactive compounds, such as fish oil, curcumin, chitosan, resveratrol and others, has emerged as safe alternatives due to their non‐toxic, non‐allergic and biodegradable nature combined with antimicrobial potential 32,42,43 . Thus, the replacement by natural agents should be a top priority during the design of therapeutic textiles providing innovative and sustainable products with antimicrobial, antioxidant and anti‐inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another key point regarding the development of therapeutic textiles with antimicrobial activity to target skin dysbiosis is the composition of such products; unfortunately, most of them comprise synthetic or metallic antimicrobial agents, which, despite being very effective against a range of microorganisms and providing durable effects on textiles, are a concern due to health hazards, action on non‐target microorganisms and environmental pollution 37,41 . Consequently, the incorporation of natural bioactive compounds, such as fish oil, curcumin, chitosan, resveratrol and others, has emerged as safe alternatives due to their non‐toxic, non‐allergic and biodegradable nature combined with antimicrobial potential 32,42,43 . Thus, the replacement by natural agents should be a top priority during the design of therapeutic textiles providing innovative and sustainable products with antimicrobial, antioxidant and anti‐inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is an ongoing study on how to combine the compound with hyaluronan [ 34 ], the use of lipid nanosystems containing resveratrol [ 35 ], organogels [ 36 ] or nanoparticles containing resveratrol. The latter are characterized by higher efficiency, among others in reducing wrinkles or inflammation of the skin compared to the classic form of polyphenol supply [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the use of lipids, especially fatty acids, to manage wound healing [ 65 , 66 ]. Fatty acids are carboxylic acids with a long hydrocarbonate chain that compound the structural components of oils and fats, among other categories of lipids [ 67 ].…”
Section: Treatments For Topical Infected Woundsmentioning
confidence: 99%
“…Other studies evaluated the effect of lipid nanocarriers containing omega-3 fatty acid or liposomes containing omega-3 fatty acid and resveratrol in cotton textile substrates as dressings for wound healing. Considering the role on inflammatory response, both formulations inhibited nitric oxide (NO) production, demonstrating an anti-inflammatory effect that improved the wound healing process [ 65 ]. Films containing lipids have been developed for application in wound care, for example, chitosan films containing oleic acid or linoleic acid and glycerol [ 84 ], that were tested on wounds in burned patients, and it was evidenced that glycerol contributed to film adhesion, and the film promoted good epithelialization in a period of 12 to 15 days.…”
Section: Treatments For Topical Infected Woundsmentioning
confidence: 99%